Kewenangan Ptun Mengadili Kasus Lingkungan (Studi Kasus Putusan 42/G/LH/2020/PTUN.MDN) - Rayhan, Ahmad; Azril, Ridwandani; Aicle, Samuel (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2023)
Environmental Pollution is one of the main problems faced by people all over the world, especially Indonesia, if there is environmental pollution, the community can complain about it to the competent court. In this study, a problem arose regarding the authority of the State Administrative Court in adjudicating environmental case disputes (DECISION 42/G/LH/2020/PTUN.MDN). The research method used is normative juridical. The findings show that Article 47 of Law Number 5 of 1986 as amended by Law Number 9 of 2004 outlines the absolute competence of the State Administrative Court in the Indonesian justice system, including its role in assessing, deciding and resolving state problems. Administrative disputes in the case of the Medan State Administrative Court certainly have absolute and relative authority in their decisions on these disputes.